Internal Jugular Vein Collapsibility Index versus Inferior Vena Cava Collapsibility Index Guided Preloading for Prevention of Spinal Anesthesia Induced Hypotension During LSCS: An Interventional Study - Pratibha Jain Shah; Pratiksha Agrawal; Madhumita Ravi Peri (Wolters Kluwer Medknow Publications, 2024)
Background and Aims: Goal directed fluid therapy (GDFT) in parturients helps to prevent spinal anesthesia induced hypotension (SAIH) and volume overload. This interventional study compared the inferior vena cava collapsibility index (IVCCI) and the internal jugular vein collapsibility index (IJVCI) guided preloading for prevention of SAIH during lower segment ceserean section (LSCS) in terms of the incidence of SAIH as the primary outcome and the total amount of fluid, mean dose of the vasopressor, the number of boluses of vasopressor required, and the incidence of intra-operative complications as secondary outcomes. Methodology: A total of 144 full-term parturients aged 20-40 years with American society of anaesthesiologists (ASA) grade II, height (140-165 cms), weight (40-70 kgs), those who were fluid responders, and those who had a window period of 1 hour before surgery under spinal anesthesia (SA) undergoing LSCS were allocated into two groups (n = 72): group IJV and group IVC. Ultrasonography (USG) guided Internal jugular vein (IJV) and Inferior vena cava (IVC) collapsibility index (CI) was recorded an hour before spinal anesthesia (SA) as per the groups assigned and preloaded accordingly. After SA, the incidence of SAIH, the requirement of vasopressor, and fluid were recorded, and side effects were managed. Results: In group IVC, the incidence of SAIH (36.84%), mean dose (3.51 ± 5.02 µg), and mean boluses (0.44 ± 0.63) of norepinephrine required to manage hypotension were significantly lower than in group IJV, and the mean goal directed fluid administered before LSCS (504.46 ± 181.48 ml) and overall mean total fluid (1104.39 ± 160.99 ml) administered were significantly higher than in group IJV. Except for shivering, the incidence of all other complications was significantly lower in group IVC (p < 0.05). Conclusion: Both IVCCI and IJVCI guided preloading are effective in combating SAIH during LSCS, but IVCCI is comparatively better than IJVCI for CI guided preloading.